Tiempos improductivos en el proceso de minado de la Compañía Minera “AC Agregados S.A.” Unidad Arequipa M (Aporte Santiaguino, 2025)
The objective of the study was to determine non-productive times by applying statistical tools in the mining process at the “AC Agregados S.A- Unidad Arequipa M Mining Company. It is a descriptive-explanatory research, with a non-experimental, cross-sectional design. The population was made up of 16 workers who work within the company's mining process. The technique of observation and timing was used. The instruments were the stopwatch, the time control sheet and the observation board. The results show three types of time in the duration of the work shift: a) Unproductive time (36%); b) Productive time (56%) and c) Authorized time (8%). It is concluded that Compañía Minera “AC Agregados S.A.” – Unidad Arequipa M has 36% of non-productive times in its operations. Of this total, three activities classified as low value-added account for 85% of non-productive time. It is concluded that the Mining Company "AC Agregados S.A.C.-Unidad Arequipa M" has 36% of non-productive times, of which three activities (few vital) represent 85% of the unproductive activities and four trivial or unimportant activities, caused by the lack of work standards of each task or unitary operation and study of methods.
Keywords: Downtime; Uptime; Authorized time; Mining